Relación entre el nivel socioeconómico de las madres que acuden a consulta en la maternidad de la ciudad de Loja y el conocimiento sobre los beneficios de la alimentación con leche materna exclusiva en el período marzomayo 2017 - Soto Carrion, Michelle Alejandra (2018)
Abstract:To determine the knowledge of mothers about the benefits of exclusive breastfeeding during the first 6 months of the child 's life, the present study was carried out with a quantitative, descriptive - transversal focus, in the maternity ward of the city of Loja; Ecuador during the period March - May 2017. The sample consisted of 100 women who attended prenatal consultation and breastfeeding period, a structured survey was applied to them about the various advantages offered by breastfeeding. The socioeconomic level was determined through the INEC 2014 survey. It was evidenced that in the women belonging to the high socioeconomic level (A) they have 67% knowledge about the general benefits of breastfeeding, the medium high level (B) 47% and the typical average level (C +) 36%. Regarding the low middle socioeconomic level (C -), it was found that 11% had high knowledge; 77% intermediate knowledge. In contrast, the low socioeconomic level (D) has only 17% knowledge about the advantages of breastfeeding.